KEANGGOTAAN INDONESIA PADA INTERNATIONAL BANK FOR RECONSTRUCTION AND DEVELOPMENT DALAM MEWUJUDKAN PEMBANGUNAN NASIONAL - Liberthin Palullungan (Paulus Law Journal, 2022)
Indonesia's membership in the International Bank for Reconstruction and Development is one step in realizing national development as the nation's ideals. This study aims to explain the scope of the IBRD related to its function and position for its member countries and to describe the status and role of Indonesia as a member of the IBRD in the context of realizing National Development. The research method used is normative or doctrinal research, which means this research is carried out using secondary data obtained indirectly but obtained through other parties, namely through library research in the form of related books, theses, journals, articles, works. writing and various information obtained through the internet with a conceptual approach and qualitative data analysis techniques. The results of this study indicate that the scope of the World Bank/IBRD is not only limited to its function in providing financial loan assistance but also technical assistance related to consulting services and strategies through national development programs. As a member of the IBRD, Indonesia has the status of a lower middle class country which was previously an upper middle class country based on Gross National Income (GNI) and has the status of a developed country in WHO which has an influence on Indonesia's national development.